Mechanical response and parametric analysis of a deep excavation structure overlying an existing subway station: A case study of the Beijing subway station expansion - Han, Jianyong; Wang, Jun; Cheng, Cheng; Zhang, Chaozhe; Liang, Erbin; Wang, Zhikang; Song, Jae-Joon; Leem, Junsu (Frontiers in Earth Science, 2023)
The existing Beijing Pingguoyuan Subway Station was extended through a extension project. The excavation for the extension was located directly above the existing station. Complex interactions exist between the existing structure and the retaining pile wall of the excavation. Based on this project, three-dimensional finite element models were established to investigate the mechanical characteristics of the embedded and non-embedded retaining pile walls. A parametric analysis was performed for both types of pile walls. The stress and deformation characteristics of the retaining pile walls and existing structures were analyzed. The results show that when the bottom of the non-embedded retaining pile walls are connected to the existing structure, the uplift of the existing structure is essentially constant; however, the maximum displacement of the pile is increased by approximately 2.7 times, and the bending moment of the pile is reduced to 57.1% of the connection condition. As the distance between the embedded retaining pile wall and the existing station increases, the uplift of the existing station increases linearly, whereas the soil between the pile and the station exhibits a non-linear increasing trend. The displacement of the embedded retaining pile wall increases as the inner force decreases. When the distance is greater than 4.7 m, the displacement and force of the pile remains essentially unchanged. The effect of the pile embedded depth on the force and deformation of the pile is mainly observed in the lower part of the pile. As the embedded depth increases, the maximum displacement decreases by approximately 16.9%, the maximum bending moment decreases, and the maximum negative bending moment increases. The key contribution of this research is to provide a prediction method for the mechanical behaviors of a expansion project. The findings from the study also provide industry practitioners with a comprehensive guide regarding the specific applications of the construction technology of a deep excavation structure overlying an existing subway station.